PERANCANGAN SISTEM INFORMASI BOOKING PADA BARBERSHOP UNTUK MEMPERMUDAH PEMESANAN - Marfin, Muhammad; Syahril, Syahril; Putri, Anju Maulidhea (LPPM Universitas Putera Batam, 2024)
This study aims to design a booking information system at a barbershop to facilitate the booking process. This system is designed to increase the efficiency of barbershop operations and improve communication with customers. Using the Waterfall development model, this system goes through the stages of needs analysis, design, implementation, and testing. The results show that the developed information system can improve customer experience by providing features such as online ordering, reminder notifications, and integration with online payment systems. In addition, the system also supports the barbershop's marketing strategy by promoting the latest services and offers, and enables data analysis to customize services according to customer preferences. The implementation of this system is expected to give barbershops a competitive edge in the ever-evolving industry.